Base Free Catalyzed Enantioselective Michael Reaction of bis(phenylsulfonyl)methane to α,β -Unsaturated Aldehydes under Iminium Activation - Alonso, Beatriz; Uria, Uxue; Carrillo, Luisa; L. Vicario, Jose; Reyes, Efraim (Current Topics in Medicinal Chemistry, 2014)
The Michael reaction of bis(phenylsulfonyl)methane with α,β-unsaturated aldehydes in the presence of catalytic amounts of a chiral secondary amine is presented. This transformation proceeds in good to excellent yields furnishing the corresponding Michael adducts in excellent enantioselectivities. Furthermore, other chiral building blocks are accessible from the obtained adducts by carrying out selective manipulation of the functional groups present at their structure, being possible to obtain a wide variety of sulfones with good results.
Keywords: Michael addition